Angiogênese tumoral - Ribeiro, José Augusto Assumpção Crespo (2023)
This article is a review of literatura about tumor angiogenesis. The early investigations, definitions and his relation with tumor growth are presented. It describes the angiogenic factors and traces the mechanism of tumor angiogenesis formation. Finally, it shows the clinical applications of these knowledges in tumor diagnosis, treatment and prognosis.